Strategies to Overcome Biological Barriers Associated with Pulmonary Drug Delivery - Adam J. Plaunt; Tam L. Nguyen; Michel R. Corboz; Vladimir S. Malinin; David C. Cipolla (MDPI AG, 2022)
While the inhalation route has been used for millennia for pharmacologic effect, the biological barriers to treating lung disease created real challenges for the pharmaceutical industry until sophisticated device and formulation technologies emerged over the past fifty years. There are now several inhaled device technologies that enable delivery of therapeutics at high efficiency to the lung and avoid excessive deposition in the oropharyngeal region. Chemistry and formulation technologies have also emerged to prolong retention of drug at the active site by overcoming degradation and clearance mechanisms, or by reducing the rate of systemic absorption. These technologies have also been utilized to improve tolerability or to facilitate uptake within cells when there are intracellular targets. This paper describes the biological barriers and provides recent examples utilizing formulation technologies or drug chemistry modifications to overcome those barriers.